2022
DOI: 10.1101/2022.05.17.22275182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing the Value of Digital Phenotyping Through Reducing Missingness: A Retrospective Analysis

Abstract: ObjectivesDigital phenotyping methods present a scalable tool to realize the potential of personalized medicine. But underlying this potential is the need for digital phenotyping data to represent accurate and precise health measurements. This requires a focus on the data quality of digital phenotyping and assessing the nature of the smartphone data used to derive clinical and health-related features.DesignRetrospective cohorts. Representing the largest combined dataset of smartphone digital phenotyping, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Like our prior studies, our research is fully reproducible. We offer details of our recruitment process and procedures in this paper that outlines details of our recruitment, screening, and data coverage procedures [ 12 ]. The mindLAMP app remains open-source software currently deployed at over 50 clinical sites worldwide, and our algorithms are also publicly accessible via GitHub [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like our prior studies, our research is fully reproducible. We offer details of our recruitment process and procedures in this paper that outlines details of our recruitment, screening, and data coverage procedures [ 12 ]. The mindLAMP app remains open-source software currently deployed at over 50 clinical sites worldwide, and our algorithms are also publicly accessible via GitHub [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This run-in period will serve to screen out participants whose devices are not able to capture digital phenotyping data or do not engage with the app at all, and give the study coordinators time to verify that informed consent is signed and dated correctly. The run-in period is designed to help improve overall digital data coverage that is important for validation of the predictive model [ 12 ]. After these 3 days, participants who have completed the required surveys and have sufficient GPS data will be moved to the enrollment period of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The passive data streams most vulnerable to missing data were the GPS and Bluetooth sensors. However, other passive sensing studies on mental health have found the opposite pattern, with more data being available from GPS than from accelerometers [ 15 , 20 , 37 ]. Sensor noncollection can occur for multiple reasons, including participants turning off the data permissions or the sensor itself.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, has implications for the integrity of the constructed variables and for understanding the potential sources of biases in the data. Sparse active data points on mood questionnaires can affect how ground truth is determined, whereas less passive data can result in inaccuracies in how features are derived and the resulting data analysis (refer to Currey and Torous [ 20 ] for an example of this).…”
Section: Introductionmentioning
confidence: 99%